Oral labetalol compared to oral nifedipine for postpartum hypertension: A randomized controlled trial - Kathryn J. Sharma; Naomi Greene; Sarah J. Kilpatrick (Taylor & Francis Group, 2017)
Objective: To determine whether oral labetalol is associated with a shorter time to blood pressure control compared to oral extended release nifedipine for management of persistent postpartum hypertension. Study Design: This randomized controlled trial conducted between June 2014 and June 2015 included women who delivered at ≥32 weeks' gestation with persistent postpartum hypertension (sustained blood pressure ≥150/100 mmHg) requiring an oral antihypertensive agent. We included women with gestational hypertension, preeclampsia, or chronic hypertension not previously on medication. Women were randomized to labetalol or nifedipine, and the allocated study drug was incrementally increased to achieve blood pressure control. The primary outcome was time to sustained blood pressure control defined as the absence of severe hypertension for at least 12 hours. Secondary outcomes included postpartum length of stay, need for increased dosing, need for additional oral antihypertensive agents, and patient reported side effects. Twenty women were needed in each group as determined by the sample size calculation. Results: We randomized 25 women to oral labetalol and 25 women to oral extended release nifedipine. The time to achieve BP control was similar between labetalol and nifedipine groups (37.6 hours versus 38.2 hours, p = 0.51). Secondary outcomes including postpartum length of stay, need for increased dosing, and need for additional oral antihypertensive agents were similar between groups. For women discharged on a single agent, significantly more subjects in the labetalol group (16/21) compared to the nifedipine group (10/22) achieved BP control with the initial starting dose (76% versus 46%, p = 0.04). No major side effects were observed. Minor side effects were significantly more common in women taking nifedipine compared to labetalol (48% versus 20%, p = 0.04). Conclusions: Both labetalol and nifedipine were effective for control of persistent postpartum hypertension. However, labetalol achieved control significantly more often with the starting dose and had fewer side effects. Clinical Trial Registration: Oral nifedipine versus oral labetalol, NCT02168309. https://clinicaltrials.gov/ct2/show/NCT02168309?term=labetalol+versus+nifedipine&rank=2